A new clerodane furano diterpene glycoside from Tinospora cordifolia triggers autophagy and apoptosis in HCT-116 colon cancer cells. (30th January 2018) - Sharma, Neha; Kumar, Ashok; Sharma, P.R.; Qayum, Arem; Singh, Shashank K.; Dutt, Prabhu; Paul, Satya; Gupta, Vivek; Verma, M.K.; Satti, N.K.; Vishwakarma, R.
Abstract: Ethnopharmacological relevance: Tinospora cordifolia is a miraculous ayurvedic herb used in the treatment of innumerable diseases such as diabetes, gonorrhea, secondary syphilis, anaemia, rheumatoid arthritis, dermatological diseases, cancer, gout, jaundice, asthma, leprosy, in the treatment of bone fractures, liver & intestinal disorders, purifies the blood, gives new life to the whole body; (rejuvenating herb) and many more. Recent studies have revealed the anticancer potential of this plant but not much work has been done on the anticancer chemical constituents actually responsible for its amazing anticancer effects. This prompted us to investigate this plant further for new potent anticancer molecules. Aim of the study: The present study was designed to isolate and identify new promising anticancer candidates from the aqueous alcoholic extract of T. cordifolia using bioassay-guided fractionation. Materials and methods: The structures of the isolated compounds were determined on the basis of spectroscopic data interpretation and that of new potent anticancer molecule, TC-2 was confirmed by a single-crystal X-ray crystallographic analysis of its corresponding acetate. The in vitro anti-cancer activity of TC-2 was evaluated by SRB assay and the autophagic activity was investigated by immunofluorescence microscopy. Annexin-V FITC and PI dual staining was applied for the detection of apoptosis. The studies on Mitochondrial Membrane potential and ROS (Reactive oxygen species) production were also done. Results: Bioassay guided fractionation and purification of the aqueous alcoholic stem extract of Tinospora cordifolia led to the isolation of a new clerodane furano diterpene glycoside (TC-2) along with five known compounds i.e. cordifolioside A (β-D-Glucopyranoside, 4-(3-hydroxy-1-propenyl)- 2, 6-dimethoxyphenyl 3-O-D-apio-β-D-furanosyl) (TC-1), β-Sitosterol(TC-3), 2β, 3β:15, 16-Diepoxy- 4α, 6β-dihydroxy-13(16), 14-clerodadiene-17, 12:18, 1-diolide (TC-4), ecdysterone(TC-5) and tinosporoside(TC-6). TC-2 emerged as a potential candidate for the treatment of colon cancer. Conclusion: The overall study on the bioassay guided isolation of T.cordifolia identified and isolated a new clerodane furano diterpenoid that exhibited anticancer activity via induction of mitochondria mediated apoptosis and autophagy in HCT116 cells. We have reported a promising future candidate for treating colon cancer. Graphical abstract: